Pemberdayaan Masyarakat melalui Pemanfaatan Tanaman Obat Tradisional di Desa Krueng Dhoe Sanggeue Kecamatan Pidie - Safrina, Safrina; Santi, Santi; Cut Suraiya Wahyuni Utami; Eva Novita (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to strengthen community capacity through an integrated educational and participatory approach in Krueng Dhoe Sanggeue Village, Pidie District. The program involved counseling, hands-on training, and continuous mentoring, and was evaluated using a pre-test and post-test design. A total of 41 medicinal plant species were identified, primarily used to treat digestive disorders, hypertension, and cough. Leaves were the most utilized plant parts (35.5%), boiling was the dominant preparation method (31.70%), and oral consumption was the main mode of use (53.65%). Most plants were sourced from household gardens (43.90%), indicating strong local resource availability. The activity resulted in a significant improvement in community knowledge regarding the proper utilization of medicinal plants. However, challenges remain in dosage standardization, safety, and processing techniques. Therefore, sustained training and structured assistance are necessary to ensure safe utilization and to optimize the health and economic potential of medicinal plant use.